The Impact of Job Embeddedness on Organizational Performance of Employees in the Ministry of Sports and Youth with the Mediating Role of Organizational Justice - Moradzadeh Khiavi, Babak; Nasiri, Mohammad; Mokhtari Yoznab, Robab (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The purpose of this study was to examine the impact of job embeddedness on the organizational performance of employees in the Ministry of Sports and Youth, considering the mediating role of organizational justice. Methodology: The present research is a descriptive-correlational study in which data were collected through a questionnaire using a field research method. The statistical population consisted of all employees of the Ministry of Sports and Youth, totaling 900 individuals. Based on Krejcie and Morgan’s table (1970), a sample of 269 employees was selected using a cluster random sampling method. Data were gathered using the Job Embeddedness Questionnaire by Crossley et al. (2007), the Organizational Performance Questionnaire by Patterson (1992), and the Organizational Justice Questionnaire by Niehoff and Moorman (1993). Findings: The face and content validity of the questionnaires were confirmed by the research supervisor, and their reliability was assessed using Cronbach’s alpha coefficient, which was calculated as 0.88 for job embeddedness, 0.75 for organizational performance, and 0.91 for organizational justice. Structural equation modeling was used for data analysis, and all calculations were performed using PLS and SPSS software. The results indicated that job embeddedness significantly affects both organizational performance and organizational justice, explaining 35.40% of the variance in organizational performance and 11.22% of the variance in organizational justice. Furthermore, organizational justice mediates the relationship between job embeddedness and the organizational performance of employees in the Ministry of Sports and Youth. Conclusion: This study highlights the negative impact of job embeddedness on organizational performance, with organizational justice as a mediating factor. Enhancing fairness, transparency, and employee engagement can mitigate these effects and improve overall productivity.